The Phenomenon of Synonymy in Communicative Phraseological Units - Ruzikulova Gulirukhsor Gofur kizi (International Journal on Integrated Education, 2021)
This article analyzes the phenomenon of synonymy of phaseological units and proverbs in Uzbek and English. It has been studied that proverbs have a feature that distinguishes them from other phraseological units, Structurally proverbs have a sentence structure with complete syntactic integrity. There are also examples of proverbs that express the content of advice, wisdom, education and aphorisms, and reflect the national cultural semantics.